A protein in pig spleen similar to immune suppressive protein of stress. - Fu Hong-Yan; Zhang Jie; Ding Gui-Feng; Fan Shao-Guang (Acta Pharmacologica Sinica, 2016)
AIM: To purify a protein in pig spleens, which was similar to immune suppressive protein of stress (ISPS), and characterize its properties and functions. METHODS: 1) Pig spleen was extracted in dilute hydrochloric acid. 2) The extract was ultra-filtrated for having high molecular weight proteins (Mr>30 000). 3) The filtrates were purified with FPLC affinity chromatography. 4) The elute from FPLC was used for T-lymphocyte proliferation and ELISA test. 5) Lastly, SDS-PAGE was used to determine the molecular weight and purity of the final product. RESULTS: A protein purified from pig spleen (the pig ISPS homologue) inhibited concanavalin A (Con A)-induced mouse lymphocyte proliferation. The molecular weight of this protein was about Mr 190 000. It has a stronger selectivity against T-lymphocyte line such as Jurkat cell line and mastocyte line (P8l5) and has a weaker inhibitory activity on macrophage line (U937). CONCLUSION: A protein similar to rat/mouse ISPS was found in pig spleen. This may provide an opportunity to study its roles in tumors and autoimmune diseases.